Serum complement C3: a determinant of cardiometabolic risk, additive to the metabolic syndrome, in middle-aged population - Onat, Altan; Hergenc, Guelay; Can, Guenay; Kaya, Zekeriya; Yuksel, Huesniye (W B SAUNDERS CO-ELSEVIER INC, 2010)
We studied whether serum complement C3 (C3) is an independent determinant of incident cardiometabolic risk (coronary heart disease [CHD], metabolic syndrome [MetS], and type 2 diabetes mellitus). A cohort of 1220 adults of a general population (age, 53 +/- 10.5 years) was evaluated prospectively at 3.3 years follow-up using Cox proportional hazard regressions. Cardiometabolic risk factors were measured. Metabolic syndrome was identified by Adult Treatment Panel III criteria modified for male abdominal obesity. The C3 levels were associated significantly and linearly with serum triglycerides, waist circumference, and C-reactive protein (CRP), and inversely with current smoking but not with the marker of insulin resistance. In regression models for incident MetS, increasing C3 quartiles strongly predicted MetS in women and in both sexes combined after adjusting for all 5 MetS components and other confounders. Circulating C3 significantly predicted in each sex incident CHD independent of age, smoking status, and presence of MetS. Even after entering CRP, C3 predicted CHD with a relative risk of 1.35 (95% confidence interval, 1.09-1.67) for I-SD increment of C3 in the total sample. Complement C3 tended to contribute, additively to MetS, to the association with diabetes with a relative risk of 1.36 in women alone, not in men. In conclusion, elevated serum complement C3 is part of the MetS cluster and confers CHD risk, additively to MetS components and CRP, in a population in which MetS prevails. Levels contribute, additively to MetS, to the diabetes risk in women alone. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: ACYLATION-STIMULATING PROTEIN; REACTIVE PROTEIN; CORONARY RISK; ASSOCIATION; DEFINITION; INSULIN; DISEASE; MARKER; MEN; Endocrinology & Metabolism